2003
DOI: 10.1021/bi034101w
|View full text |Cite
|
Sign up to set email alerts
|

Ascaris suum NAD-Malic Enzyme Is Activated by l-Malate and Fumarate Binding to Separate Allosteric Sites

Abstract: The kinetic mechanism of activation of the mitochondrial NAD-malic enzyme from the parasitic roundworm Ascaris suum has been studied using a steady-state kinetic approach. The following conclusions are suggested. First, malate and fumarate increase the activity of the enzyme in both reaction directions as a result of binding to separate allosteric sites, i.e., sites that exist in addition to the active site. The binding of malate and fumarate is synergistic with the K(act) decreasing by >or=10-fold at saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…Site-directed mutagenesis studies indicated that 2 amino acid residues were found to be implicated in this activation: Arg-105 (homologous to R91 of human NAD(P)-ME) and Lys-143 (Fig. 4A) (17). The effect of malate on A. suum NAD-ME is opposite to the effect of this substrate on C 4 -NADP-ME (Fig.…”
Section: The Allosteric Binding Site For Fumarate and Malate As Activmentioning
confidence: 96%
See 3 more Smart Citations
“…Site-directed mutagenesis studies indicated that 2 amino acid residues were found to be implicated in this activation: Arg-105 (homologous to R91 of human NAD(P)-ME) and Lys-143 (Fig. 4A) (17). The effect of malate on A. suum NAD-ME is opposite to the effect of this substrate on C 4 -NADP-ME (Fig.…”
Section: The Allosteric Binding Site For Fumarate and Malate As Activmentioning
confidence: 96%
“…On the other hand, Ascaris suum NAD-ME is activated by both malate and fumarate, which bind to different binding sites that act synergically (17). Site-directed mutagenesis studies indicated that 2 amino acid residues were found to be implicated in this activation: Arg-105 (homologous to R91 of human NAD(P)-ME) and Lys-143 (Fig.…”
Section: The Allosteric Binding Site For Fumarate and Malate As Activmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the differential expression pattern observed is consistent with AtGenExpress The region with the most significant differences is underlined. The amino acid residues homologous to the residues involved in fumarate activation of human NAD(P)-ME and A. suum NAD-ME are indicated in light gray (33,41,42). The arrow indicates the site where the sequences of NAD-ME1 and -2 were exchanged for the generation of the chimeric proteins NAD-ME1q and -2q.…”
Section: Coa Activation Of Nad-me2 and Nad-meh-mentioning
confidence: 99%